Can item response theory reduce patient burden when measuring health status in neurological disorders? Results from Rasch analysis of the SF-36 physical functioning scale (PF-10). Issue 2 (1st August 2001) - Jenkinson, C; Fitzpatrick, R; Garratt, A; Peto, V; Stewart-Brown, S
Abstract : BACKGROUND: Indices of physical function may have a hierarchy of items. In cases where this can be demonstrated it may be possible to reduce patient burden by asking them to complete only those items which relate directly to their own level of ability. OBJECTIVES: To determine whether statistical procedures, operationalising what is known as item response theory (IRT), can be used to assess the unidimensionality of the 10 item physical functioning domain of the SF-36 in patients with Parkinson's disease and motor neuron disease, and, secondly, to determine whether it would be possible to administer subsets of items to certain patients, on the basis of their replies to other items in the scale, thereby reducing patient burden. METHODS: Rasch analysis, a form of IRT methodology, of the 10 item physical functioning domain (PF-10) in two neurological patient samples was undertaken and the results compared with results of a Rasch analysis of data gained from a population survey (the third Oxford healthy lifestyles survey). RESULTS: Evidence from the analyses suggests that the PF-10 does not form a perfect hierarchy on a unidimensional scale. However, certain items seem to form a hierarchy, and responses to some of them are contingent on responses to the other items. CONCLUSIONS: Rasch analysis of the PF-10 in neurological patients has indicated that certain items of the scale are hierarchically ordered, and consequently not all respondents would need to complete them all: indeed those most severely ill would be required to complete less items than those with only limited disabilities. The implications of this are discussed.